Potentialities and weaknesses of the patient safety climate: Scoping review (Research, Society and Development, 2021)
Objectives: to map the studies that used the Safety Attitudes Questionnaire in critical hospital units; identify the strengths and weaknesses of the patient safety climate through the domains of the instrument and relate strengthening strategies for patient safety. Method: Scoping Review carried out in the databases of Latin American and Caribbean Literature in Health Sciences, Public / Publisher Medical Literature Analysis and Retrievel System Online, Cumulative Index to Nursing and Allied Health Literature, Scopus; Web of Science, Joanna Briggs Institute Library of Systematic Reviews and other sources with studies published between 2006 - 2020 that used the Safety Attitudes Questionnaire instrument. Results: Included 25 studies that evaluated the safety climate in the Surgical Center and Intensive Care Unit. A weak security climate was evidenced with scores below the recommended. In the assessment of the scores of the six domains of the instrument, the data from the included studies pointed out “Perception of management” as the weakest point and “Job Satisfaction” was the only item that had a strong score. Strategies for improving the quality of care and strengthening patient safety have been suggested in the studies, such as in-service education and the implementation of adverse event reporting systems. Conclusion: This study made it possible to recognize the strengths and weaknesses mapped in the literature, which favors planning for the construction of new health care practices, in the quality of care and in organizational development.